The case for central bank independence: A review of key issues in the international debate - Rodolfo Dall'Orto Mas; Benjamin Vonessen; Christian Fehlker; Katrin Arnold (European Central Bank (ECB), 2020)
This Occasional Paper analyses how significant expansions in central banks' mandates, roles and instruments can result in challenges to the independence of monetary policy. The paper reviews, in particular, some of the key challenges to central bank independence brought about by the global financial crisis (GFC) of 2007 and assesses their impact on the de jure and de facto independence of selected central banks around the world in the past few years. It finds that although the level of de jure (legal) central bank independence did not deteriorate, the level of de facto (actual) independence of the central banks of some of the largest economies in the world may have weakened. The paper presents counterarguments to the key critiques raised against central banks due to their policy response during the GFC, and concludes that the case for central bank independence is as strong as ever.
Keywords: B1; B2; C4; E3; E4; E5; E6; K3; N1; N2; 330; central bank independence; central bank mandate; financial stability; global financial crisis; price stability